Design of the Death Penalty as a Legal Instrument for Combating Corruption Crimes - Abdul Wahid (LEGAL BRIEF, 2022)
There are two opinions, especially the death penalty, causing controversy over the regulation of the death penalty as a legal instrument to combat corruption. There are those who agree with the imposition of the death penalty and some people in fact question the basis for the justification of the sentence which does not provide opportunities for criminals to improve to become good human beings. In fact, the death penalty for cases of corruption has never been imposed, so the threat of capital punishment cannot be used as an ultimum remedium against perpetrators of corruption. The form of crime and the punishment system in corruption crimes deviates from the general criminal system, namely regarding the form and system of imposing the punishment, regarding the severity of the main crime to be imposed, the maximum limit for each crime has been determined, while the specific minimum limit is not determined, but the general minimum limit. , for example imprisonment and imprisonment for a minimum of one day. In the criminal law of corruption, two main types of criminal sanctions are imposed simultaneously, which are imperative, between imprisonment and fines. - additional types of crime. Imperative-facultative system. It is suggested the need for amendments to the Law on the Eradication of Criminal Acts of Corruption by formulating capital punishment for all acts of corruption without any special criteria such as a disaster situation because of its large impact on society, nation and state, so that it becomes the ultimum remedium. The need for judges to impose severe criminal sanctions, so that it can create a deterrent effect for corruptors and other people who have the opportunity to commit corruption are reluctant or afraid to commit acts that violate the law because the criminal sanctions are heavy.